The Influence of Brand Image, Celebrity Endorser, Electronic Word of Mouth and Communication Media on Purchase Decisions - Syifaramadan, Choiruddin; Rahayu, Tri Septin Muji; Utami, Restu Frida; Purwidianti, Wida (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the influence of brand image, celebrity endorser, electronic word of mouth and communication media on purchasing decisions for skincare brand S products in Indonesia. The population in this study was the general public of Kembaran sub-district. The sampling method used was purposive sampling. The formula for determining the minimum sample used Slovin with a minimum sample of 100 respondents. The instrument used was a questionnaire with a Likert scale. This study used multiple linear regression test analysis tools. The results showed that brand image had a positive and significant effect on purchasing decisions, celebrity endorsers had a significant positive effect on purchasing decisions, electronic word of mouth had a negative effect on purchasing decisions and communication media had no impact on purchasing decisions.